Pharmacogenomics of brain cancer and personalized medicine in malignant gliomas. (August 2008) - Mehrian Shai, Ruty; Reichardt, Juergen KV; Chen, Thomas C
The pharmacogenetics of cancer treatment has been aimed at identifying genetic components of interindividual variability in patients'' response to cancer chemotherapy and toxicity. This, in turn, will establish an individually based treatment, and also elucidate the molecular basis of the treatment regimen for further improvements. Brain cancer is an instructive example for the potential contributions of pharmacogenomics to improved treatment in the 21st century. Patients with oligodendrogliomas have benefited from phamacogenomics, as there is a clear relationship between response to chemotherapy and chromosomal profile. Drug efficacy, safety and response could be improved by using pharmacogenomics to identify genetic markers that differentiate responder from nonresponder patient groups, as well as identifying patients likely to develop adverse drug reactions. This review will focus on how pharmacogenomics by microarray studies may lead to much more accurate tumor classification, drug and biomarker discovery, and drug efficacy testing. We will discuss relevant scientific advances in pharmacogenetics for more personalized chemotherapy.